Socialization of emotion regulation strategies through friends. (8th April 2016) - Reindl, Marion; Gniewosz, Burkhard; Reinders, Heinz
ABSTRACT: This study examines the effects of best friends' emotion regulation strategies (regarding the emotions anger, fear, and sadness) on the development of adolescents' emotion regulation strategies and subsequent depressive symptoms. Based on a two‐wave longitudinal sample of 238 German adolescents, true change analyses showed positive effects of best friends' adaptive strategies (T1) on the change of adolescents' adaptive strategies (T2 − T1) for anger and fear. Best friends' adaptive strategies (T1) indirectly influence the development of maladaptive strategies (T2 − T1) through the change of adaptive strategies (T2 − T1) and, in turn, the development of depressive symptoms (T2 − T1; two‐step mediation). Best friends' adaptive strategies for sadness did not have an effect on adolescents' adaptive strategies. In contrast to adaptive strategies, none of the friends' maladaptive strategies affected adolescents' maladaptive strategies. The results are discussed in terms of peer influences on the development of emotion regulation strategies and psychosocial adjustment.